Does HIV Infection Alter Parkinson Disease?. (1st October 2015) - Moulignier, Antoine; Gueguen, Antoine; Lescure, François-Xavier; Ziegler, Marc; Girard, Pierre-Marie; Cardon, Bernard; Pialoux, Gilles; Molina, Jean-Michel; Brandel, Jean-Philippe; Lamirel, Cédric
Abstract : Objective: To describe the clinical features, treatment(s), and outcomes of 15 HIV-infected patients with idiopathic Parkinson disease (PD) and sustained virus suppression and immunologic reconstitution, from a reference cohort of 9847 persons living with HIV (PLH). Methods: This retrospective, single-center matched case–control 1:2 study included PLH-PD patients evaluated over a 12-year period (2002–2013) with mean follow-up of 6.5 years. PD clinical features and dopamine replacement therapy (DRT) were compared, and biologically relevant HIV data were assessed. Results: PD prevalence in PLH was similar to that of the general population. At onset, clinical presentations and therapeutic management were similar for both groups. Rapidly effective DRT was well tolerated without combined antiretroviral therapy interactions or virus escape. At the end of the follow-up, compared with HIV-negative PD, PLH had a significantly lower median Unified Parkinson's Disease Rating Scale motor score (4 vs 14; P < 0.001), median Hoehn and Yahr stage (1 vs 2; P = 0.0005), and median Handipark scale score (2 vs 3; P = 0.0036) under the same daily DRT. One PLH underwent highly successful deep brain stimulation of the subthalamic nucleus. Conclusions: HIV-associated PD is similar to idiopathic PD with some features suggesting an HIV-induced functional adaptation of dopaminergic neurons that might counterbalance the PD-induced neuronal loss. Concurrent HIV infection does not compromise the outcome of idiopathic PD.